Language practices in Namibian primary schools - Norro Soili (Taylor & Francis, 2022)
The main focus of the article is on teachers’ classroom language practices in eight primary schools in Oshana and Khomas school regions. Language ideologies and translanguaging practices were used as a theoretical framework to evaluate the language ecologies that were created by the language practices in the schools included in the research study.
The data consist of 140 responded questionnaires, 19 individual interviews and eight focus group discussions with teachers, and 47 observed lessons. Mixed methods were used to analyse the data. Questionnaire responses were analysed quantitatively except for open-ended questions. Qualitative content analysis was used to analyse the interviews and focus group discussions as well as the observed lessons.
The results show that despite teachers’ efforts to gear the classroom language practices towards a more multilingual language ecology by using different multilingual strategies, the prevailing hierarchical language ideologies, reinforced by the assessment that is done in English only, contribute to maintaining the dominant position of English compared to the local languages.